2022
DOI: 10.1002/jpen.2336
|View full text |Cite
|
Sign up to set email alerts
|

Hypermagnesemia and feeding intolerance in preterm infants: A cohort study

Abstract: Background: Feeding intolerance (FI) is a common clinical problem in preterm infants often caused by some neonatal disorders and drugs, including antenatal exposure to magnesium sulfate (MgSO 4 ).Objective: To evaluate the association between hypermagnesemia at birth and FI in preterm infants during the first 72 h of life.Method: This was a cohort study conducted with preterm infants aged <34 weeks' gestation. Infants presenting at least two of the following signs were considered as having FI: vomiting, abdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…There are reports that it influences the transition to full enteral feeding and is associated with delayed feeding tolerance (24,25). It has been revealed that the serum magnesium concentration of newborns applied antenatal MgSO4 is higher than normal during the first 72 hours of life, especially in premature infants, and that this situation was linked to feeding intolerance (26). In our study, antenatal magnesium prophylaxis was found to be significantly associated with an increased risk of feeding intolerance.…”
Section: Discussionsupporting
confidence: 48%
“…There are reports that it influences the transition to full enteral feeding and is associated with delayed feeding tolerance (24,25). It has been revealed that the serum magnesium concentration of newborns applied antenatal MgSO4 is higher than normal during the first 72 hours of life, especially in premature infants, and that this situation was linked to feeding intolerance (26). In our study, antenatal magnesium prophylaxis was found to be significantly associated with an increased risk of feeding intolerance.…”
Section: Discussionsupporting
confidence: 48%